PPM Mixed Inter-team Bowling Tournament 2010 - Suja', Balqis (Persatuan Pustakawan Malaysia, 2011)
Report of a bowling tournament held on 18th December 2010 at Ampang Super Bowl, Ampang point, Kuala Lumpur.